Predictive effect of resilience on self-efficacy during the COVID-19 pandemic: The moderating role of creativity - Xu, Yanhua; Yang, Guang; Yan, Chongshan; Li, Jiatong; Zhang, Jingwei (Frontiers in Psychiatry, 2022)
Introduction To appraise the relationship and mechanism between resilience and self-efficacy in the context of the COVID-19 pandemic, we proposed a model to investigate the effect of resilience on self-efficacy and the moderating effect of creativity in this regard. Methods Scales that measured resilience, creative behavior, and self-efficacy were rated by 881 college students in China to establish the moderating model. Results The results showed that resilience and self-efficacy of participating college students were positively correlated, which meant that high resilience could predict a high level of self-efficacy. Moderating analysis using the SPSS PROCESS plug-in showed that creativity was an important element of resilience that positively affected self-efficacy and that this moderating effect was more significant in participants with a high degree of creativity. Discussion These findings can provide a better understanding of the relationship between resilience and self-efficacy in demonstrating the traumatic impact of the COVID-19 pandemic on adolescent mental health and academic performance.